Composition optimisation and performance evaluation of waterborne epoxy resin emulsified asphalt tack coat binder for pavement. Issue 11 (19th September 2022) - Fu, Hao; Wang, Chaohui; Niu, Liangliang; Yang, Guolin; Liu, Luqing
ABSTRACT: To ensure the effective bonding of each structural layer of pavement and improve the service quality and durability of pavement, the waterborne epoxy resin (WER) emulsified asphalt (WEREA) tack coat binders were prepared by using polyurethane-epoxy resin. The basic properties of WEREA, such as tensile strength, adhesion to aggregate, high temperature heat resistance and low temperature impact resistance were studied. Its composition and ratio were optimised. The waterproof, bonding and durability performance of WEREA used in pavement tack coat were evaluated. The results show that WEREA prepared by polyether polyurethane modified E-51 epoxy resin (PUD-E51) has higher early and late strength. Its tensile strength was 1.75 MPa after curing for 7 days. The basic properties of WEREA, including adhesion to aggregate, heat resistance and impact resistance were better than those of SBS modified asphalt and crumb rubber modified asphalt binder. The tack coat of WEREA cannot seep under the dynamic water pressure of 0.6 MPa for 30 min. According to the interlaminar shear strength, the recommended spraying amount of the WEREA tack coat was 1.0 kg/m 2 . The WEREA could guarantee the effective bonding of each structural layer of the pavement, and improve the durability of the tack coat and pavement.